2019
DOI: 10.1080/17512433.2019.1637731
|View full text |Cite
|
Sign up to set email alerts
|

A combined, bioidentical, oral, 17β-estradiol and progesterone capsule for the treatment of moderate to severe vasomotor symptoms due to menopause

Abstract: Introduction: Many women seek treatment to alleviate menopausal vasomotor symptoms (VMS). Numerous women use combination compounded hormone therapy (CHT) to achieve the benefits of estrogen/progesterone for endometrial protection. TX-001HR is a combination of bioidentical 17βestradiol (E2) and progesterone (P4) in a single capsule designed for continuous daily use to treat moderate to severe VMS. Areas covered: This drug profile describes the efficacy and safety of 4 doses of this E2/P4 (mg/mg: 1/ 100, 0.5/100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…In this context, great hopes are being pinned on the first approved oral combination drug for MHT called Bijuva®, containing a low dose of 17β-oestradiol and micronised progesterone. Both compounds, which are the active substances of this drug, are molecularly and chemically identical to the endogenous hormones oestradiol and progesterone [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, great hopes are being pinned on the first approved oral combination drug for MHT called Bijuva®, containing a low dose of 17β-oestradiol and micronised progesterone. Both compounds, which are the active substances of this drug, are molecularly and chemically identical to the endogenous hormones oestradiol and progesterone [13].…”
mentioning
confidence: 99%
“…In the REPLENISH trial, a total of 1,835 female subjects were randomised to one of four groups receiving combined E2/P4 products containing different doses of hormones (1 mg E2/100 mg P4, 0.5 mg E2/100 mg P4, 0.5 mg E2/50 mg P4, 0.25 mg E2/50 mg P4) or placebo [14]. The results of the REPLENISH trial were presented in three key publications [14][15][16] and in approximately a dozen other papers containing post-hoc analyses of the trial's outcomes [10,13,[17][18][19][20][21][22][23][24][25] This study presents the conclusions of the REPLENISH trial regarding exclusively the subjects who were treated with the product approved as Bijuva®, i.e. oestradiol 1 mg + progesterone 100 mg (E2/P4-1/100), focusing on the pharmacokinetic characteristics, clinical efficacy, and safety profile of the drug.…”
mentioning
confidence: 99%
“…32 A recent study showed 1 year of combined 17 β-estradiol plus micronized progesterone resulted in similar rates of abnormal mammograms as placebo (3.7% versus 3.1%). 33 Other Cancers. Eighteen years of follow-up from the WHI showed similar total cancer mortality rates in the pooled intervention group (8.2%) and the placebo (8.0%): HR, 1.03; 95%CI, 0.95-1.12.…”
Section: Clinical Datamentioning
confidence: 99%
“…At the end of the first year of the WHI study, the incidence of abnormal mammograms was 9.4% in women taking conjugated equine estrogen/MPA versus 5.4% for placebo 32 . A recent study showed 1 year of combined 17 β‐estradiol plus micronized progesterone resulted in similar rates of abnormal mammograms as placebo (3.7% versus 3.1%) 33 …”
Section: Estrogenmentioning
confidence: 99%
“…4 In addition to GSM, vasomotor symptoms (VMS) such as hot flashes and night sweats are experienced by 50% to 80% of menopausal women. 5 Therefore, a need exists for effective treatment of menopausal symptoms whether it be short-term for VMS or longer term for GSM.…”
Section: Introductionmentioning
confidence: 99%